ALGORITHM FOR THE TREATMENT OF PATIENTS WITH CHRONIC HEART FAILURE WITH REDUCED LEFT VENTRICULAR EJECTION FRACTION - E. V. Reznik; I. G. I.G. Nikitin (SINAPS LLC, 2018)
Despite a significant number of publications devoted to the care of patients with chronic heart failure (CHF), a practicing doctor is not always easy to navigate in the use of medicines and indications for high-tech methods of treatment in these patients. The largest evidence base is currently accumulated in patients with CHF with a reduced left ventricular ejection fraction (CHFrEF), which is characterized by a significant decreasing in the quality of life, decreased/lost ability to work, disability of patients and high mortality. This article details all the essential medicines used for therapy of CHFrEF, the sequence and practical aspects of their prescribing in accordance with contemporary guidelines. The issue of treating patients with CHF refractory to standard therapy, including with the help of a new class of drugs from the group of angiotensin receptor neprilysin inhibitor, cardiac resynchronization therapy, implantation of cardioverter-defibrillators and application of devices for mechanical circulatory support and heart transplantation is considered. The publication is illustrated by tables, figures, diagrams, which makes it accessible for understanding and memorizing.